AN STUDY ON THE ABILITY OF THE FIRST-YEAR STUDENTS OF INTERNATIONAL CLASS OF MAN 2 KOTA PEKANBARU IN WRITING DESCRIPTIVE - Syahregina Alyuvany; Erni Erni; M. Syarfi M. Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The research design of this study was descriptive research that focused on quantitative approach. The objective of this study was to find out the level of students’ ability in writing descriptive text at the first-year students of international class of MAN 2 Kota Pekanbaru. The students’ writing ability was analyzed according to the analytic scoring rubric by Brown (2007). The sample of this study was selected by using the total sampling technique, which 34 students of X MIPA 6, as known as international class. The writer used a written test as the primary data. The collected data were analyzed by the three raters. The findings of this study revealed that the students’ ability in writing descriptive text can be categorized as a very good level with the average score of 86.45. Based on the result of the students’ ability in each writing aspect, the highest score was in the content aspect (92.4) while the lowest score was in the mechanics aspect (79.41).Key Words: Study, Writing Ability, Descriptive Text